OPTIMASI PROSES PEMBUATAN GULA CAIR BERBAHAN BAKU PATI JAGUNG MANIS MENGGUNAKAN METODE HIDROLISIS ENZIMATIS DAN EVAPORATOR BERTEKANAN - Riko, Muhamad; Dewi, Erwana (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2025)
The demand for sugar in Indonesia continues to increase, both in the form of sucrose (cane sugar) and liquid sugar. However, domestic sugarcane production remains insufficient. This limitation encourages the search for alternative sweeteners that can be locally produced, one of which is liquid sugar derived from starch through enzymatic hydrolysis. This study utilized sweet corn starch hydrolyzed using α-amylase and glucoamylase enzymes, followed by concentration using a pressurized evaporator. The objective of this research is to determine the optimum conditions in the production process of liquid sugar from sweet corn starch. The hydrolysis process was carried out by varying the enzyme volume at 0.8 ml, 1.0 ml, and 1.2 ml. The hydrolysate was then concentrated using a pressurized evaporator at a temperature of 130 °C and a pressure of 1.2 bar, with evaporation times ranging from 20 to 95 minutes. Based on the research results, the optimum process conditions were obtained at an enzyme volume of 1.2 mL with an evaporation time of 80 minutes. Under these conditions, the resulting product had the highest sugar content of 55.98% with a pH of 4.84, total dissolved solids of 65%, air content of 40.76%, and ash content of 0.609%.